Prosesi Seremonial dan Makna Makan Patita di Negeri Oma - Maluku: The Ceremonial Procession and Meaning of Makan Patita in Negeri Oma - Maluku - Jenny Koce Matitaputty; Ida Masinay (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Makan Patita is a tradition of communal feasting or eating together among Maluku communities that practiced in festivity the Panas Pela, Panas Gandong, King coronation, building Baileo house, the celebration of city`s anniversary day, and other events in Ambon city. However, for the people of Negeri Oma in Haruku Island, the tradition of Makan Patita differs from others. The differences are attracted to be discussed about the ceremonial procession and its meaning of the tradition of Makan Patita in Negeri Oma. This research aims to describe the ceremonial process and its meaning of the Makan Patita Soa practiced in Negeri Oma, Haruku Island District, Central Maluku Regency, Maluku Province, Indonesia. This is a qualitative research where the data source obtained purposively and the data collection techniques by using observation, interview, and documentation. The results showed that: 1) Makan Patita in Negeri Oma is divided into two types; first, the uncle feeds his nephew/child (Mara/Marei), and also the nephew/child feeds his uncle (ana kas makang om). There are three stages in the practice of Makan Patita tradition; the initial stage, a time-set meeting, and preparation of various things, both food and a long white table and the prayers of struggle in Baileo Kotayasa by the Bapa Lima-Lima. In the second stage, the Makan Patita begins with Cakelele dances and the ceremonial procession takes children to the Patita dining table, then the uncles feed their nephews. In the final stage, each remaining food must be brought back and eaten by all children at home, then covered with a Eucharistic prayer for the Soa and Maradansa. 2) The meaning of Makan Patita tradition for the people in Negeri Oma is kinship ties, respect, and appreciation for elders (uncles) and it contains the symbolic meaning of hope to the children in the Soa will become a good generation and remain in the fellowship of siblings.